La serie pictórica del Apóstol Santiago en el Templo Santiago Apóstol de Lampa-Puno, de Isidoro Moncada - Palomino Arana, Flor Isabel (2018)
Analyzes the pictorial series dedicated to the Apostle Santiago, located in the temple Santiago Apostle of Lampa, Puno, Peru. The series is a set of eleven paintings attributed to the artist Cusquenian Isidoro Francisco Moncada, active in the Collao region during the second half of the eighteenth century. It unveils a pictorialseries little disseminated and not studied, which is addressed from the perspective of the history of art, using sources and tools of the disciplines of history. The analysis focuses on the findings of the engravings that served as a source of inspiration to the artist.